Patient Safety Program for Oral Surgery Services at Hospital at Universitas Sumatra Utara - Rianda Dwi Magfirah Lubis; Zulfendri Zulfendri; Siti Khadijah (RIRAI Publisher, 2023)
This research uses qualitative research with a phenomenological approach conducted in-depth interview. Samples of 7 people working in USU hospitals. The results of the study analyzed 6 patient safety targets and 8 contributor factors. Implementation of Implementation of Patient Identification Using Min 2 Identity in Patient Bracelets and Stickers, Confirming Identity Before Medical Actions, Effective Communication is done Readback/ Tulbakon, Writing Patient Referrals with SBAR, Beware of High Alert Drugs by prescribing drugs into pharmacy and storing lidocaine and ephineprin in special containers there are high-alert stickers In X -ray photos and informed consent, prevention and control of infection risk is done hand washing, use of PPE, use of a safe needle and removing sharp objects in a safety box, the risk of falling risk is carried out the patient's review process, giving yellow bracelets and patient assistance. Patient contributors, differences in perception and emotional levels affect the occurrence of incidents. Factors of officers such as fatigue and double work are the cause of stressors. SPO is available at the hospital, can be accessed at any time. Communication factors are carried out verbally and non-verbally. The work environment, the building is appropriate, but the maintenance of facilities and infrastructure is not good, resulting in a postponement of care for patients. The leadership supports the staff but reporting is a weak point because of the lack of staff awareness in reporting incidents. Team factors there are differences in quantity between nurses and doctors. Educational factors are required repetition of patient safety orientation to the staff. Hospitals are advised to improve infrastructure, evaluate the quantity and qualification of the team and increase awareness in reporting incidence.